1 Slash 100%: gamification of mathematics with hybrid QR-based card game - Ong C. Yung; Syahrul N. Junaini; Ahmad A. Kamal; Laili F. Md Ibrahim (Institute of Advanced Engineering and Science, 2020)
Mathematics is vital in our life and society. However, gamification of mathematics is rare for topics such as fractions and decimals. This paper presents the development of an educational mathematics game called one slash one hundred percent (1 Slash 100%). It is the hybridization of the conventional card game and quick response (QR). This research aims to study how the respondents explore the card game to master decimal, fraction and percentage. The testing was conducted among secondary school students in Kuching, Sarawak, Malaysia (n=12; age=14). The respondents were asked to answer a set of questions in pre-test and post-test question. The results are promising where the analysis showed a significant difference between pre-test (M=14.3, SD=2.103) and post-test scores (M=17.6, SD=2.234). Thus, gamification of mathematics using the hybrid card game increases their mastery of decimal, fraction and percentage.